Moral Knowledge - Johnson, Oliver A. author. aut Link
172 p.
Keywords: As its title indicates, this book is concerned with two different fields of philosophy, ethics and epistemology. The bulk of the argument is devoted to epistemological questions, as these arise within the context of morality. Hence, the conclusions I reach could probably best be described as prolegomena to the elaboration of a theory of ethics. I have plans, which I hope will be realized in the next few years, of elaborating such a theory. I started work on Moral Knowledge in the summer of 1958 with the help of a University Faculty Fellowship, for which I am most grateful. of the research for the book, as well as a good bit of its writing, Much was done in two libraries, The University Library, Berkeley, and the Bodleian Library, Oxford. Members of the staffs of both libraries, by their courtesy and helpfulness, lightened immeasurably the task of my research. lowe a special debt of gratitude to four people-to Mr.